George Wilson's vision of early Victorian science and technology - Channell, David F., 1945- author.
1 online resource.
Keywords: "This volume is a comprehensive study of George Wilson, a leading advocate for evangelical science and for the role of biology in technology, it examines his work to develop a unitary vision of Victorian science and technology by drawing upon religion, transcendental natural history and Baconian philosophy. George Wilson was the first Professor of Technology at the University of Edinburgh and the founding Director of the Industrial Museum of Scotland (now the National Museum of Scotland). Throughout his career he lectured and published on a wide range of topics, including the prospect of life on other planets, the history of science, natural theology, chemistry and poetry. His works were very popular, he was praised by Charles Dickens and his lectures drew large audiences, particularly women. Wilson sought to educate people about the significant scientific and technological developments taking place during the first half of the nineteenth century and create a unitary vision of science and technology"--